Fairness and Accountability : Engaging in Health Systems in the Middle East and North Africa - World Bank (Washington, DC, 2013)
The World Bank Health Nutrition and Population Sector Strategy for MENA (2013-2018). The new Health, Nutrition, and Population (HNP) Strategy for the Middle East and North Africa (MENA) region is a very timely initiative in light of the transformative socio-political changes in the region, and of the World Bank Group's renewed commitment to ending poverty and reducing inequality. To protect, promote, and preserve the health of its people, health systems in the region must aspire to become more fair and accountable. The MENA HNP strategy is envisioned as a dynamic 'living' strategy, rather than as a static document, providing a compass for prioritization of World Bank engagements in line with regional and client country needs. Its implementation spans three phases. Phase one will involve an intensive engagement process aimed at listening to client needs and clarifying the issues and options towards building and maintaining fairer and more accountable health systems. Phase two entails development of country specific engagement plans in each country. Phase three consists of actual implementation of the strategy, spanning over a period of about four years. Fairness in health and health systems refers to the absence of systematic disparities in health that could be avoided through prevention and care; the just distribution of the burden of costs of health care according to people's ability to pay; and an equitable response to the nonmedical needs, rights, and expectations of those seeking and obtaining health care-that is for a dignified interaction with the provider. Accountability refers to the obligation to ensure that health care services are timely, effective, safe, appropriate, cost-conscious, and patient-centered. The nexus of accountability in health care governs the interaction among three key players: populations, payers, and providers. Safeguarding fairness and accountability requires that the health system is fiscally sound and sustainable. Finally, accountability of providers refers to those interventions that modulate performance through financial and non-financial provider incentives, workforce planning to meet human resources for health, and by setting up alternate organization of care modalities in low resource settings.